Menuju Demokrasi Rasional: Melacak Pemikiran Jürgen Habermas tentang Ruang Publik - Antonius Galih Prasetyo (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2012)
As a concept widely employed to promote the deeper and more radical democracy within the framework of deliberative democracy, public sphere as formulated by Jürgen Habermas in his two books, The Structural Transformation of Public Sphere and Between Facts and Norms, acts as a crucial theory to investigate and assess the degree of publicness in today’s democracy discourse. This paper aims to elaborate the concept of public sphere as written in those two books. By comparing the content of each book, this paper also classifies the similarity and differences between the concept of public sphere written in those two texts.